2008
DOI: 10.1164/rccm.200709-1356oc
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fluticasone with or without Salmeterol on Systemic Biomarkers of Inflammation in Chronic Obstructive Pulmonary Disease

Abstract: ICS in conjunction with long-acting beta(2)-adrenergic agonist do not reduce CRP or IL-6 levels in serum of patients with COPD over 4 weeks. They do, however, significantly reduce serum SP-D levels. These data suggest that these drugs reduce lung-specific but not generalized biomarkers of systemic inflammation in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
5
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 54 publications
10
106
5
14
Order By: Relevance
“…We were unable to confirm this finding, and so do others recently [24]. Anyway, there is no convincing evidence, at present, that inhaled corticosteroids are effective in reducing the all-cause mortality rate in COPD [25].…”
Section: Discussioncontrasting
confidence: 58%
“…We were unable to confirm this finding, and so do others recently [24]. Anyway, there is no convincing evidence, at present, that inhaled corticosteroids are effective in reducing the all-cause mortality rate in COPD [25].…”
Section: Discussioncontrasting
confidence: 58%
“…However, a prospective study of high-dose ICS in COPD patients (TORCH study) showed a minimal reduction in all causes of mortality, indicating that it is unlikely that there is a significant clinical benefit of ICS on COPD comorbidities such as cardiovascular disease or lung cancer, which are the commonest causes of death [93]. A controlled trial of high-dose ICS with or without a LABA showed no reduction in systemic inflammation in COPD patients, as measured by circulating IL-6 and CRP concentrations, indicating likely corticosteroid resistance of systemic as well as local inflammation in COPD patients [164]. However, there was a reduction in SP-D, indicating that ICS may reduce the production of lung-specific markers of inflammation.…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%
“…Thus, ICS therapy leads to a reduction in systemic levels in inflammatory markers such as C-reactive protein or surfactant-D [68,69].…”
Section: Anti-inflammatory Effects Of Ics In Copdmentioning
confidence: 99%